Pengajaran noun-pronoun agreement bagi mahasiswa Business English - Hasriani G; Mardiyanah Nasta (Universitas Negeri Makassar, 2019)
The partner of this service program was the second semester students of Business English Study Program, Faculty of Language and Literature, State University of Makassar. The problem of partner was the lack of knowledge regarding conformity between noun and pronoun in an English sentence so that they continue to make mistakes in writing or expressing an English sentences. The expected outcome was the students have an understanding of noun-pronoun agreements in English and can make English sentences correctly both in oral and written form. The approach used in conducting this program consisted of two methods, namely the presentation and practice. The results achieved were the participants (1) have knowledge and understanding that are likely not at the same level regarding the basic theories of noun-pronoun agreement, (2) are able to adjust between pronoun with the noun that precedes the pronoun (antecedent) in an English sentence, and (3) around 95% are able to do exercises in accordance with the theories in oral or written form even though some of them or about 5% are sometimes still wrong in writing or saying the sentence in English.